Socio‑Cultural Capital and Endogenous Growth in Coastal Capture Fisheries: A Study of Sangihe, North Sulawesi - Lungari, Fitria Fresty; Palawe, Handoko Jayaputra; Sirait, Evi (Journal of Economic Growth and Development Review, 2025)
This study examines the role of socio-cultural capital as a driver of endogenous economic growth in coastal capture fisheries, focusing on the Sangihe Islands in North Sulawesi, Indonesia. Based on qualitative fieldwork, including interviews, participant observation, and community profiling, the research identifies six key mechanisms through which social and cultural factors support local economic development: intergenerational knowledge transfer, customary resource governance, trust-based labor and credit systems, communal risk management, cultural identity as economic motivation, and internal differentiation within social structures. These findings show that economic growth in Sangihe is deeply embedded in informal institutions and cultural practices, which function as productive assets. By framing growth as an internally driven process rooted in local relationships and values, the study offers a more holistic and context-sensitive understanding of development in small-scale fisheries. The results carry significant implications for policy, highlighting the need to recognize, protect, and integrate socio-cultural capital into strategies for sustainable and inclusive coastal development.